Pairwise alignment of DNA sequence using hypercomplex number representation - Shu, Jian Jun (2011)
A new set of DNA base-nucleic acid codes and their hypercomplex number representation have been introduced for taking the probability of each nucleotide into full account. A new scoring system has been proposed to suit the hypercomplex number representation of the DNA base-nucleic acid codes and incorporated with the method of dot matrix analysis and various algorithms of sequence alignment. The problem of DNA sequence alignment can be processed in a rather similar way as pairwise alignment of protein sequence.